KESANTUNAN BERBAHASA DALAM DISKUSI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS NEGERI MAKASSAR - Hamsidar; Usman; Baharman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to describe the forms of politeness in student discussions. This type of research is qualitative with a descriptive design. Data collection techniques include observation, notes, and recording the forms and functions of politeness expressed in student discussions. Data analysis techniques are carried out through data transcription, data reduction, data presentation, and conclusions. The results of the study indicate that the forms of politeness in the classroom have fulfilled the six maxims starting from the maxim of wisdom/wisdom, the maxim of generosity, the maxim of praise/appreciation, the maxim of humility/simplicity, the maxim of agreement/agreement and the maxim of sympathy. However, it was revealed that the maxim of generosity was the most frequently found in student speech while the maxim of humility was the least found. Thus, it can be concluded that the class has fulfilled the overall impression of language, although it still needs to be strengthened on the maxim of humility.